IMPLEMENTASI PROGRAM BADAN USAHA MILIK DESA (BUMDes) DI DESA MEKAR BARU KECAMATAN DATUK TANAH DATAR KABUPATEN BATU BARA - Emelia Dewi Sukowati; Februati Trimurni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
The Mekar Baru Village Government formed a Village-Owned Enterprise (BUMDes) as the driving force for the village economy, but in its formation there was still minimal guidance from the Regional Government so that several problems emerged, including the lack of training provided to the community in managing BUMDes, lack of socialization to the community, lack of supervision carried out so that BUMDes are not running optimally and there is a lack of government assistance in providing solutions to problems faced by BUMDes. The purpose of this study was to find out how the Implementation of the Village Owned Enterprises (BUMDes) Program in Mekar Baru Village, Datuk Tanah Datar District, Batubara Regency. The research method used is descriptive with a qualitative approach. Data collection was carried out through interviews, observation and documentation. The data obtained were then analyzed qualitatively using the Implementation Theory of Van Metter dan Van. The results showed that Standards and Objectives of the BUMDes program are not clear because the local government has not formulated a clear implementation process. Resources are still lacking such as competent Human Resources in managing BUMDes. The communication of the Implementing Body built by BUMDes is still lacking. Characteristics of the Implementing Agency which does not show alacrity in inviting the community to participate in BUMDes activities. The economic environment influences the community to choose to participate in the BUMDes. The attitude of the Mekar Baru BUMDes executors who are slow to respond to the needs of the community. The attitude of the Executor as an Implementor is also not fast and responsive in resolving the problems faced by BUMDes Mekar Baru, this is due to the lack of funds owned.